2022
DOI: 10.1111/1475-6773.14053
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patient, physician, and practice characteristics predicting the use of low‐value services

Abstract: Objective: To examine characteristics of beneficiaries, physicians, and their practice sites associated with greater use of low-value services (LVS) using LVS measures that reflect current care practices.Data Sources: This study was conducted in the context of a large, nationwide primary care redesign initiative (Comprehensive Primary Care Plus), using Medicare claims data in 2018. Study Design:We examined beneficiary-level total counts of LVS based on the existing 31 claims-based measures updated by excluding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Examine provider‐ and organizational‐level characteristics that predict the use of low‐value care 94 and develop strategies to foster de‐implementation of low‐value care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examine provider‐ and organizational‐level characteristics that predict the use of low‐value care 94 and develop strategies to foster de‐implementation of low‐value care.…”
Section: Resultsmentioning
confidence: 99%
“…86 Address cultural relevance (i.e., attention to culture, values, and interactions) when examining fidelity of EBIs for historically marginalized populations. Examine provider-and organizational-level characteristics that predict the use of low-value care 94 and develop strategies to foster de-implementation of low-value care.…”
Section: Approaches and Processesmentioning
confidence: 99%
“…Clinician characteristics include biological sex, race-ethnicity, specialty, and region. Clinician characteristics have been shown to correlate with practice patterns 32,33 . Although the region is a broad measure, it is common for clinicians to interact with clinicians outside of their immediate geographical area via the Internet, conferences, and print media.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we adjusted for physician characteristics in the models: gender, geriatric training (because a previous study showed different patterns of EOL care by physicians' geriatric training status 38 ), health system affiliation (because a previous study indicated different care patterns by physicians' health system affiliation status [39][40][41][42] ), and the number of attributed beneficiaries (categorized into tertiles). We used physician-level data by Doximity, a professional networking platform for physicians in the U.S. 43,44 and defined physicians' geriatric training as (1) those with a self-reported specialty of geriatric medicine in the MD-PASS data and/or (2) those with board certification in geriatric medicine (both active and inactive) through the American Board of Internal Medicine (ABIM) in the Doximity data.…”
Section: Adjustment Variablesmentioning
confidence: 99%